International news coverage in the United States media - Ortiz Vazquez, Vickie M. (My University, 2003)
United States media has the power to enlighten the American public about other countries. The media, however, chooses to portray a distorted picture. Previous studies have concluded that there is a lack of international news coverage and that international coverage, when it does exist, is sensational, negative and related to United States interest in some way. This paper will explores to what extent the media utilized by the classified and unclassified staff of a Midwestern university falls in the same categories as previous studies. A survey was developed to identify the two forms of media most utilized by individuals from a Midwestern university. Television (CNN) and radio (NPR/WPR) were chosen as the two primary media. These two media forms were then subjected to a content analysis to explore to what extent the international event characteristics still exist today. The study concluded that the characteristics of international events found in previous studies still apply to international news coverage today.
Thesis Chair, Dr. Sue Wildermuth. This file was last viewed in Adobe Reader 7.0
Keywords: Foreign news--United States; Mass media and public opinion--United States; Public opinion--United States; Mass media--Psychological aspects